Fulfilling a need in Armenia: the creation of the Occupational Therapy guidebook for inclusion - Babikian, Victoria
In Armenia children with disabilities are often stigmatized and separated from the community. Some are sent to institutions or orphanages, some are hidden in the home, and others are hastily placed into schools and ignored in classrooms. However, Armenia is moving towards a more inclusive society. Victoria Armineh Babikian volunteered with Children of Armenia Charitable Fund (COAF) in 2017; she was their first ever Occupational Therapist. She introduced a different perspective- providing holistic care by addressing self-care needs and enhancing physical, cognitive, and sensory skills for children with intellectual and developmental disabilities. Upon completion of her volunteer experience, Babikian needed a sustainable approach to continue increasing knowledge on the care of children with disabilities. Therefore, she compiled the Occupational Therapy Guidebook to Inclusion, an 80-page manual that provides clear information about common diagnoses, simple exercises, and functional activities using homemade tools to enhance strength, coordination, cognitive processing, sensory regulation, and behavior among children with disabilities. This guidebook will be published and distributed throughout Armenia. The purpose of the Occupational Therapy Guidebook to Inclusion is to enhance disability resources for every region of Armenia, especially within rural communities.
Keywords: Occupational therapy